Problems of application and possible ways to improve the institute of affiliated persons in the Russian Federation - Baranov S. A. (Socio-Pedagogical Issues of Education and Upbringing, 2025)
A comprehensive study of the main theoretical and practical aspects of the institute of affiliated persons in the Russian legal reality in its systemic correlation forms the subject of this author's work. The article reveals the legislative structure of affiliation, its doctrinal interpretation in the context of various legal segments. The conclusion is substantiated that it is necessary to adopt a single federal law as a kind of author's intention, its final result in the context under study, taking into account all the legal nuances of recognition and activity of affiliated persons in the Russian Federation in order to avoid negative legal consequences of various kinds and properties.
Keywords: взаимозависимые лица; предпринимательская деятельность; entrepreneurial activity; affiliation; affiliated persons; legal categories; connectedness; legal gap; interdependent persons; аффилированность; аффилированные лица; юридические категории; связанность; правовой пробел